Perbedaan Hasil Belajar Siswa Menggunakan Bimbingan Belajar Online - Annur Fitri Hayati (Universitas Negeri Padang, 2020)
This study aims to analyze whether there are differences in learning outcomes of students who take online tutoring and students who do not take tutoring. The population of this study was the students of class X in Padang 3 high school who took Ruangguru online tutoring and the sample technique used was proportional random sampling using the Slovin formula so that the number of samples obtained was 58 students. The hypothesis of this study was tested using One Way Aonva analysis. The results showed that there was no difference in the average learning outcomes between groups of students who took Ruangguru online tutoring and groups of students who did not take tutoring.